3. PERSEPSI DAN PARTISIPASI MASYARAKAT LOKAL DALAM PENGELOLAAN TAMAN NASIONAL GUNUNG RINJANI PULAU LOMBOK - Lalu Sukardi; Dudung Darusman; Leti Sundawati; Hardjanto Hardjanto (JURNAL AGRIMANSION, 2009)
ABSTRACT The general goal of this research is to define perception and participation of local community in Rinjani Montain National Park (RMNP) preservation. This research was conducted in five resorts of RMNP, those are Senaru, Santong, Stiling, Aikmel, and Sembalun resort. Data were analyzed descriptively, scoring (lickert scale), spearman correlation, and Contingen Valuation Methods (CVM). The result of this research showed that the communities perception is grouped into medium category. The community realized the function of RMNP is to protect them from flood, eroded, storm. They also knew that forest resources of RMNP has a high economic value. However, the economic pressure forced the communities to exploite the forest (incluing timber). On the other hand, the communities participatory on RMNP managment is low. Communities involvement in RMNP prservation need economic insentive and has positif relation to household income.